2021
DOI: 10.1186/s12885-021-08519-8
|View full text |Cite
|
Sign up to set email alerts
|

Beta-hydroxy beta-methylbutyrate/arginine/glutamine (HMB/Arg/Gln) supplementation to improve the management of cachexia in patients with advanced lung cancer: an open-label, multicentre, randomised, controlled phase II trial (NOURISH)

Abstract: Background Cancer cachexia causes significant morbidity and mortality in advanced lung cancer patients. Clinical benefit of β-hydroxy-β-methylbutyrate, arginine, and glutamine (HMB/Arg/Gln) was assessed in newly diagnosed patients. Methods NOURISH, a prospective, two-arm, open-label, multi-centre, randomised controlled phase II trial compared cachexia in patients who received HMB/Arg/Gln with those who did not. All patients received structured nutr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…Combined medical therapy using MA and fish oil, dronabinol, or NSAIDs resulted in no changes in weight or appetite compared to MA alone ( 21 , 22 ). Beta-hydroxy beta-methyl butyrate/arginine/glutamine(HMB/Arg/Gln) may work together to decrease muscle damage from reactive oxygen species and pro-inflammatory cytokine; however, recent data demonstrated that HMB/Arg/Gln supplementation couldn't improve the loss of lean body mass in patients with advanced lung cancer ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Combined medical therapy using MA and fish oil, dronabinol, or NSAIDs resulted in no changes in weight or appetite compared to MA alone ( 21 , 22 ). Beta-hydroxy beta-methyl butyrate/arginine/glutamine(HMB/Arg/Gln) may work together to decrease muscle damage from reactive oxygen species and pro-inflammatory cytokine; however, recent data demonstrated that HMB/Arg/Gln supplementation couldn't improve the loss of lean body mass in patients with advanced lung cancer ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, other investigators have also found that modulating Gln intake in patients with lung cancer may result in different outcomes. Jennifer Pascoe et al evaluated Beta-hydroxy betamethylbutyrate/arginine/glutamine (HMB/Arg/Gln) in newly diagnosed lung cancer patients, but ultimately found that HMB/Arg/Gln reduced the odds of treatment success, contrary to the hypothesis (93). Gln did not demonstrate a corresponding effect on radiotherapy-induced esophagitis in the study by Abdul Rahman Jazieh et al consistently, which may be due to the specific combination of chemotherapeutic agents or inappropriate doses of Gln (86).…”
Section: Relieving Complications Through Altering Gln Intakementioning
confidence: 99%
“…The 48 articles were classified into the following categories: full text peer-reviewed manuscripts (n = 38), conference abstracts (n = 8), and clinical trial registrations (n = 2). Of the full text peer-reviewed manuscripts, the majority reported on randomized controlled trials (RCTs) (n = 18) [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51], followed by quasi-experimental trials (n = 15) [52][53][54][55][56][57][58][59][60][61][62][63][64][65][66], retrospective cohort observational studies (n = 2) [67,68], and case studies (n = 3) [69][70][71]. Conference abstracts reported on RCTs (n = 3) [72][73][74], quasi-experimental trials (n = 4) [75][76][77][78], and a case study (n = 1) [79].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Arginine was the main dietary supplement investigated in an RCT where it was administered in the form of a specially formulated enteral formula and replaced 41% of casein [36], as well as in an observational study where it was given in the form of an immunonutrition enteral formula (Impact ® ) containing 12.5 g/L L-arginine, dietary nucleotides, EPA, and docosahexaenoic acid (DHA) [67]. Arginine was investigated as part of a combined treatment with glutamine (amino acid) and β-hydroxyl β-methyl butyrate (HMB) (amino acid metabolite) in three studies (two RCTs [35,45] and one quasi-experimental trial [57]), which were also the only studies where glutamine or HMB were included. Daily doses were in the following ranges: 14-28 g arginine, 14-28 g glutamine, and 2.4-6 g HMB daily [35,45,57].…”
Section: Proteins and Amino Acidsmentioning
confidence: 99%
See 1 more Smart Citation